2018
DOI: 10.1007/s00261-018-1467-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performances of intravoxel incoherent motion and conventional diffusion-weighted imaging in the differential diagnosis of benign and malignant portal vein thrombus

Abstract: ADC values might be more superior tool than IVIM parameters in differentiation between malignant and benign PVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
1
2
0
2
Order By: Relevance
“…Our findings support the observations of previous studies in which DW signal intensity and ADC measurements were found to reliably distinguish between benign and malignant PVT in patients with HCC; the vascularity of the thrombus, as well as the presence of malignant cells, may have affected both DW signal intensity and ADC values of the thrombi (2,(22)(23)(24). Furthermore, our results showed that CEUS findings correlated well with DWI-MRI findings; CEUS findings may be more accurate, especially for the diagnosis of malignant PVT with infiltrative HCC.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings support the observations of previous studies in which DW signal intensity and ADC measurements were found to reliably distinguish between benign and malignant PVT in patients with HCC; the vascularity of the thrombus, as well as the presence of malignant cells, may have affected both DW signal intensity and ADC values of the thrombi (2,(22)(23)(24). Furthermore, our results showed that CEUS findings correlated well with DWI-MRI findings; CEUS findings may be more accurate, especially for the diagnosis of malignant PVT with infiltrative HCC.…”
Section: Discussionsupporting
confidence: 91%
“…Use of multimodal MRI, especially the ADC parameter, can help to distinguish between benign and malignant PVTs. Aumann et al (23) reported that the ADC value can effectively differentiate benign and malignant PVTs, with sensitivity and specificity values of 80.0% and 72.7%, Patients with PVT from January 2011 to April 2016 (n=564) Excluded:…”
Section: Discussionmentioning
confidence: 99%
“…The use of an increased number of b-values leads to extended acquisition time and motion artefacts. Respiratory triggered sequences can reduce the respiratory motion artefacts [21]. Although we used respiratory navigation, we excluded 3 patients due to motion-related artefacts.…”
Section: Discussionmentioning
confidence: 99%